Saturn's auroral morphology and field-aligned currents during a solar wind compression - Badman,SV; Provan,G; Bunce,EJ; Mitchell,DG; Melin,H; Cowley,SWH; Radioti,A; Kurth,WS; Pryor,WR; Nichols,JD; Jinks,SL; Stallard,TS; et al. (Icarus, 2016)
On 21–22 April 2013, during a coordinated auroral observing campaign, instruments onboard Cassini and the Hubble Space Telescope observed Saturn’s aurora while Cassini traversed Saturn’s high latitude auroral field lines. Signatures of upward and downward field-aligned currents were detected in the nightside magnetosphere in the magnetic field and plasma measurements. The location of the upward current corresponded to the bright ultraviolet auroral arc seen in the auroral images, and the downward current region was located poleward of the upward current in an aurorally dark region. Within the polar cap magnetic field and plasma fluctuations were identified with periods of ∼20 and ∼60 min. The northern and southern auroral ovals were observed to rock in latitude in phase with the respective northern and southern planetary period oscillations. A solar wind compression impacted Saturn’s magnetosphere at the start of 22 April 2013, identified by an intensification and extension to lower frequencies of the Saturn kilometric radiation, with the following sequence of effects: (1) intensification of the auroral field-aligned currents; (2) appearance of a localised, intense bulge in the dawnside (04–06 LT) aurora while the midnight sector aurora remained fainter and narrow; and (3) latitudinal broadening and poleward contraction of the nightside aurora, where the poleward motion in this sector is opposite to that expected from a model of the auroral oval’s usual oscillation. These observations are interpreted as the response to tail reconnection events, initially involving Vasyliunas-type reconnection of closed mass-loaded magnetotail field lines, and then proceeding onto open lobe field lines, causing the contraction of the polar cap region on the night side.